Drug education games for youth - Heitor Martins Pasquim; Cassia Baldini Soares; Ricardo Santoro (Social Medicine Publication Group, 2016)
This integrative review aims to explore the goals of drug education games for youth and to propose recommendations based on a collective health framework. A database search was conducted of five sources and grey literature, using the following inclusion criteria: theoretical, observational, experimental, or qualitative studies that described or analyzed educational games to prevent or treat drug use in young individuals (15-29 years of age). Eight different games were presented in 16 articles. Results indicate that the majority of games do not allow creativity or unexpected answers, although a few exceptions were found. These games also ignore economic, historical, and cultural aspects of the drug phenomenon, aligning with the War on Drugs ideology and therefore favoring a "hooked leisure." Despite these flaws, the games have some potential applications that allow us to recommend them in daily practice as methods of educational process.